Minimally invasive cone beam CT-guided evacuation of parenchymal and ventricular hemorrhage using the Apollo system: proof of concept in a cadaver model. (1st July 2014) - Fiorella, David; Arthur, Adam; Schafer, Sebastian
Abstract : Introduction: The Apollo system (Penumbra Inc, Alameda, California, USA) is a low profile irrigation–aspiration system designed for the evacuation of intracranial hemorrhage. Objective: To demonstrate the feasibility of using Apollo in combination with cone beam CT guidance. Methods: Parenchymal (n=1) and mixed parenchymal–intraventricular hematomas (n=1) were created in cadaver heads using a transvascular (n=1) or transcranial (n=1) approach. Hematomas were then imaged with cone beam CT (CB-CT), and the long axis of the hematoma defined. The CB-CT data were then used to guide transcranial access to the hematoma—defining the location of the burr hole and the path to the leading edge of the hematoma. An 8F vascular sheath was then placed under live fluoroscopic guidance into the hematoma. A second CB-CT was performed to confirm localization of the sheath. The hematoma was then demarcated on the CB-CT and the Apollo wand was introduced through the 8F sheath and irrigation–aspiration was performed under (periodic) live fluoroscopic guidance. The operators manipulated the wand within the visible boundaries of the hematoma. After irrigation–aspiration, a control CB-CT was performed to document reduction in hematoma volume. Results: Transvascular and transcranial techniques were both successful in creating intracranial hematomas. Hematomas could be defined with conspicuity sufficient for localization and volumetric measurement using CB-CT. Live fluoroscopic guidance was effective in navigating a sheath into the leading aspect of a parenchymal hematoma and guiding irrigation–aspiration with the Apollo system. Irrigation–aspiration reduced the parenchymal hemorrhage volume from 14.8 to 1.7 cc in 189 s in the first case (parenchymal hemorrhage) and from 26.4 to 4.1 cc in 300 s in the second case (parenchymal and intraventricular hemorrhage). Conclusions: The cadaver model described is a useful means of studying interventional techniques for intracranial hemorrhage. It seems feasible to use CB-CT to guide the evacuation of intraparenchymal and intraventricular hemorrhage using the Apollo system through a minimally invasive transcranial access.